International judicial dispute in the bank transfer process - محمد, يحيى; متري , موسى خليل (Latakia University Journal - Economic and Legal Sciences Series, 2022)
At least three parties involved in the implementation of the bank transfer, namely the orderer, the bank and the beneficiary, and a dispute may arise when executing the bank transfer from one country to another, accordingly the competent court is required to consider the dispute between the court of the ordering country, the country of the beneficiary or the country of the bank and this is done according to the rules of attribution in the country in which one of the parties initiated the case.